Industry Support of Medical Research: Important Opportunity or Treacherous Pitfall? - Tierney, William M.; Meslin, Eric M.; Kroenke, Kurt (Journal of general internal medicine : JGIM, 2016)
Pharmaceutical and device manufacturers fund more than half of the medical research in the U.S. Research funding by for-profit companies has increased over the past 20 years, while federal funding has declined. Research funding from for-profit medical companies is seen as tainted by many academicians because of potential biases and prior misbehavior by both investigators and companies. Yet NIH is encouraging partnerships between the public and private sectors to enhance scientific discovery. There are instances, such as methods for improving drug adherence and post-marketing drug surveillance, where the interests of academician researchers and industry could be aligned. We provide examples of ethically performed industry-funded research and a set of principles and benchmarks for ethically credible academic–industry partnerships that could allow academic researchers, for-profit companies, and the public to benefit.